The exploring microstructural, caloric, and corrosion behavior of NiTiNb shape-memory alloys - Mohammed, Safar Saeed; Balci, Esra; Qadir, Hussein Ahmed; Qader, Ibrahim Nazem; Saydam, Sinan; Dagdelen, Fethi (Springer, 2022)
The influence of four different quantities of niobium (Nb) on some physical and chemical properties of Ni-Ti alloy was examined in this study. Furthermore, the effect of thermal cycling at different temperatures on some thermodynamic parameters was examined. The arc melting technique was conducted for the sample fabrication procedure. Differential scanning calorimetry (DSC) with different heating rates was utilized to investigate the impact of Nb additive on transformation temperatures and some thermal properties of the Ni-Ti-Nb SMAs. Also scanning electron microscopy (SEM) was used to investigate the microstructural properties of samples, and the microhardness of all samples was determined by the Vickers microhardness technique. The transformation temperatures and other thermodynamic parameters, such as; enthalpy change, entropy change, elastic energy, and Gibbs free energy, were decreased by both Nb additive and thermal cycling, however, it increased the temperature hysteresis of the martensitic phase transformation. Nb additive diminished the activation energy, while had an opposite effect on the microhardness of the Ni-Ti-Nb alloy. The corrosion resistance test results also demonstrated that Nb has a positive effect on the biocompatibility improvement in Ni-Ti alloy because it increased the corrosion resistance of the SMAs.
Keywords: Ni-Ti-Nb; Shape-memory alloy; Corrosion resistance; Microstructure; Thermal activation energy